Homocysteine and arterial thrombosis: Challenge and opportunity - Di Minno, Matteo N. D.; Tremoli, Elena; Coppola, Antonio; Lupoli, Roberta; Minno, Giovanni Di (Thrombosis and Haemostasis, 2010)
The correlation between homocysteine and vascular disease has been assessed in several clinical studies that demonstrated that elevation of plasma total homocysteine (tHcy) was an independent risk factor for atheriosclerotic disease. Major advances of homocysteine metabolism disorders have been made during the last few years, encompassing the rare homozygous enzyme deficiencies, as well as more common milder abnormalities. In experimental and clinical studies, a homocysteine-mediated oxidant stress has been shown to trigger platelet activation, in turn leading to a tendency to thrombosis, in patients with severe hyperhomocysteinaemia. Likewise, the hypomethylation hypothesis on acquired hyperhomocysteinaemia (chronic renal disease) and the interrelationship between hyperhomocysteinaemia and impaired fibrinolysis, have added further biological plausibility to the role for hyperhomocysteinaemia in vascular medicine. However, whether hyperhomocysteinaemia is causal or a marker of vascular disease, and whether plasma tHcy is only an indicator of the metabolic status remains to be clarified. The role of the intake of some vitamins (folic acid, vit.B12, vit.B6) on cardiovascular disease (CVD) is poorly understood: in spite of the lowering of homocysteine (Hcy) levels, vitamin supplementation failed to exert significant effects on cardiovascular risk. On the other hand, although some lipid-modifying treatments increase Hcy levels in diabetics, there is no evidence that this attenuates the beneficial effects of such treatments on the cardiovascular risk. Because of these uncertainties in the area, the data available do not provide support for routine screening and treatment for elevated Hcy to prevent CVD.
Keywords: Homocysteine; arterial thrombosis; folate